In every heartbeat - Sawyer, Kim Vogel (Bethany House, 2010)
As three friends who grew up in the same orphanage head off to college together, they each harbor a cherished dream. Libby wishes to become a famous journalist, Pete plans to study to become a minister, and Bennett wants to join a fraternity and have as much fun as possible. But as tensions rise around the world on the brink of World War I, the friends' differing aspirations and opinions begin to divide them, as well. And when Libby makes a shocking discovery about Pete's family, will it drive a final wedge between the friends or bond them in ways they never anticipated?